Accuracy of an automated three‐dimensional technique for the computation of femoral angles in dogs. (12th October 2019) - Longo, Federico; Savio, Gianpaolo; Contiero, Barbara; Meneghello, Roberto; Concheri, Gianmaria; Franchini, Federico; Isola, Maurizio
Abstract : Aims: The purpose of the study was to evaluate the accuracy of a three‐dimensional (3D) automated technique (computer‐aided design (aCAD)) for the measurement of three canine femoral angles: anatomical lateral distal femoral angle (aLDFA), femoral neck angle (FNA) and femoral torsion angle. Methods:Twenty‐eight femurs equally divided intotwo groups (normal and abnormal) were obtained from 14 dogs of different conformations (dolicomorphic and chondrodystrophicCT scans and 3D scanner acquisitions were used to create stereolithographic (STL) files, which were run in a CAD platform. Two blinded observers separately performed the measurements using the STL obtained from CT scans (CT aCAD) and 3D scanner (3D aCAD), which was considered the gold standard method. C orrelation coefficients were used to investigate the strength of the relationship between the two measurements. Results: A ccuracy of the aCAD computation was good, being always above the threshold of R 2 of greater than 80 per cent for all three angles assessed in both groups. a LDFA and FNA were the most accurate angles (accuracy >90 per cent). Conclusions: The proposed 3D aCAD protocol can be considered a reliable technique to assess femoral angle measurements in canine femur. The developed algorithm automatically calculates the femoral angles in 3D, thus considering the subjective intrinsic femur morphology. The main benefit relies on a fast user‐independent computation, which avoids user‐related measurement variability. The accuracy of 3D details may be helpful for patellar luxation and femoral bone deformity correction, as well as for the design of patient‐ specific, custom‐made hip prosthesis implants.